(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
This article presents research on the cultivation and development of 16 varieties of Dutch tulips in the soil and climatic conditions of the Namangan region. The main objective of the study was to determine the optimal options for the timing and rates of irrigation when growing tulip varieties.